Systematic Investigation of the Effect of Non-Ionic Emulsifiers on Skin by Confocal Raman Spectroscopy-A Comprehensive Lipid Analysis - Yali Liu; Dominique Jasmin Lunter (MDPI AG, 2020)
Non-ionic emulsifiers are commonly found in existing pharmaceutical and cosmetic formulations and have been widely employed to enhance the penetration and permeation of active ingredients into the skin. With the potential of disrupting skin barrier function and increasing fluidity of stratum corneum (SC) lipids, we herein examined the effects of two kinds of non-ionic emulsifiers on intercellular lipids of skin, using confocal Raman spectroscopy (CRS) with lipid signals on skin CRS spectrum. Non-ionic emulsifiers of polyethylene glycol alkyl ethers and sorbitan fatty acid esters were studied to obtain a deep understanding of the mechanism between non-ionic emulsifiers and SC lipids. Emulsifier solutions and dispersions were prepared and applied onto excised porcine skin. Water and sodium laureth sulfate solution (SLS) served as controls. SC lipid signals were analysed by CRS regarding lipid content, conformation and lateral packing order. Polyethylene glycol (PEG) sorbitan esters revealed no alteration of intercellular lipid properties while PEG-20 ethers appeared to have the most significant effects on reducing lipid content and interrupting lipid organization. In general, the polyoxyethylene chain and alkyl chain of PEG derivative emulsifiers might indicate their ability of interaction with SC components. HLB values remained critical for complete explanation of emulsifier effects on skin lipids. With this study, it is possible to characterize the molecular effects of non-ionic emulsifiers on skin lipids and further deepen the understanding of enhancing substance penetration with reduced skin barrier properties and increased lipid fluidity.